Sclerostin attenuates the mechanical loading response in trabecular bone - Khalid, Kamarul Ariffin; Kogawa, Masakagi; Findlay, David M; Atkins, Gerald J (2012)
Osteocytes play a major role in normal bone maintenance and have recently been implicated in a number of conditions that affect bone. Sclerostin is an osteocyte secreted protein, deficiency of which was found to be causative of the high bone mass phenotype in patients with sclerosteosis and van Buchem's disease. Mechanical loading of bone within the anabolic range decreases osteocyte sclerostin expression. An anti-sclerostin antibody, currently undergoing clinical trials, has been developed as a bone anabolic agent. Recent evidence from in vitro and in vivo experiments shows that osteocytes, via sclerostin, downregulate osteoblastogenesis (anti-anabolic) and potentiate osteoclastogenesis procatabolic) activity.